Mannose-binding lectin genotypes: lack of association with susceptibility to thoracic empyema. - Chapman, S; Vannberg, F; Khor, C; Rautanen, A; Maskell, N; Davies, C; Moore, C; Day, N; Crook, D; Davies, R; Hill, A (BioMed Central, 2010)
BACKGROUND: The role of the innate immune protein mannose-binding lectin (MBL) in host defence against severe respiratory infection remains controversial. Thoracic empyema is a suppurative lung infection that arises as a major complication of pneumonia and is associated with a significant mortality. Although the pathogenesis of thoracic empyema is poorly understood, genetic susceptibility loci for this condition have recently been identified. The possible role of MBL genotypic deficiency in susceptibility to thoracic empyema has not previously been reported. METHODS: To investigate this further we compared the frequencies of the six functional MBL polymorphisms in 170 European individuals with thoracic empyema and 225 healthy control individuals. RESULTS: No overall association was observed between MBL genotypic deficiency and susceptibility to thoracic empyema (2 x 2 Chi square = 0.02, P = 0.87). Furthermore, no association was seen between MBL deficiency and susceptibility to the Gram-positive or pneumococcal empyema subgroups. MBL genotypic deficiency did not associate with progression to death or requirement for surgery. CONCLUSIONS: Our results suggest that MBL genotypic deficiency does not associate with susceptibility to thoracic empyema in humans.